IMPLEMENTASI ASEAN ECONOMIC COMMUNITY (AEC) DI INDONESIA TAHUN 2016-2020 - Ike Rahma Ningsih; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ASEAN The ASEAN Economic Community (AEC) is a form of economic integration undertaken by ASEAN member countries to create a safe, dynamic, and economically integrated region. This paper aims to analyze the implementation of the AEC focusing on the policies and regulations adopted by the Indonesian goverment from 2016-2020. This study uses economic integration theory, a liberal perspective, and the library research method. This study uses secondary data from various sources such as journals, books, reports, and official websites. The implementation of the AEC in Indonesia involves concrete steps taken by the government to implement and enforce AEC-related policies and commitments. This article also discusses the challenges faced in the implementation process and analyzes Indonesia's economic performance within the framework of the AEC. The AEC is an economic integration initiative between ASEAN member countries aimed at creating a single market and integrated production base, promoting fair competition, enhancing connectivity, and achieving equitable economic development in the region. Keywords: ASEAN Economic Community (AEC), implementation, Indonesia